Consequences of Inhibiting Amyloid Precursor Protein Processing Enzymes on Synaptic Function and Plasticity - Hui Wang; Andrea Megill; Kaiwen He; Alfredo Kirkwood; Hey-Kyoung Lee (Neural Plasticity)
Alzheimer's disease (AD) is a neurodegenerative disease, one of whose major pathological hallmarks is the accumulation of amyloid plaques comprised of aggregated β-amyloid (Aβ) peptides. It is now recognized that soluble Aβ oligomers may lead to synaptic dysfunctions early in AD pathology preceding plaque deposition. Aβ is produced by a sequential cleavage of amyloid precursor protein (APP) by the activity of β- and γ-secretases, which have been identified as major candidate therapeutic targets of AD. This paper focuses on how Aβ alters synaptic function and the functional consequences of inhibiting the activity of the two secretases responsible for Aβ generation. Abnormalities in synaptic function resulting from the absence or inhibition of the Aβ-producing enzymes suggest that Aβ itself may have normal physiological functions which are disrupted by abnormal accumulation of Aβ during AD pathology. This interpretation suggests that AD therapeutics targeting the β- and γ-secretases should be developed to restore normal levels of Aβ or combined with measures to circumvent the associated synaptic dysfunction(s) in order to have minimal impact on normal synaptic function.